Aluminum plastic film and application thereof
By using aluminum-plastic films with aluminum foil layer, adhesive layer and nylon layer in lithium-ion batteries, using phase change materials and through-hole structures, the high silicon-based anode material of lithium-ion batteries is solved under high voltage and thermal abuse conditions. The safety performance issues significantly improve the thermal safety performance and aesthetics of the battery.
Patent Information
- Application Number
- CN202411315508.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The safety performance of high silicon-based negative electrode materials in lithium-ion batteries deteriorates under high voltage and thermal abuse conditions, which can easily lead to a sharp increase in the internal temperature of the battery cell and even cause fire or explosion. The existing technology has not effectively solved this problem.
Aluminum plastic film including an aluminum foil layer, an adhesive layer and a nylon layer is used. The adhesive layer is filled with phase change material, and through holes are provided on the nylon layer to form air convection to improve the heat dissipation rate and enhance the thermal impact of the battery. Pass rate.
By optimizing the structure and material of aluminum-plastic film, the thermal safety performance of lithium-ion batteries is significantly improved, the battery cell temperature is reduced, the risk of thermal runaway and spontaneous combustion is avoided, and the overall aesthetics and structural integrity of the battery are maintained.
Smart Images

Figure CN119261319A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to an aluminum-plastic film and application thereof. Background Art
[0002] Soft-packaged lithium-ion batteries are widely used in various digital products and mobile devices due to their advantages such as high energy density, low self-discharge, wide operating temperature range, and no environmental pollution. With the upgrading of products, electronic products, especially portable mobile communication tools, have evolved from simple text and voice communication to communication tools and entertainment devices that integrate text, voice, images, videos and other multi-information and multimedia. The functions of electronic products are constantly improving and increasing, which leads to the continuous increase of power consumption.
[0003] One of the ways to increase capacity in the industry is to select a negative electrode active material for lithium-ion batteries with a higher gram-to-gram capacity. Currently, silicon is the negative electrode active material with the highest known specific capacity, with a gram-to-gram capacity of 4200mAh / g. Compared with graphite negative electrode materials, silicon also has a higher lithium deintercalation potential, which can effectively avoid the precipitation of lithium during high-rate charge and discharge, and can improve the safety performance of lithium-ion batteries; but in the negative electrode, if the proportion of silicon gradually increases, or the operating voltage of the lithium-ion battery increases, the safety performance of the lithium-ion battery may gradually deteriorate. Specifically, when a lithium-ion battery including a high-voltage silicon-carbon negative electrode (10% SiC) is subjected to thermal abuse testing, the external temperature rise will cause a chemical reaction inside the battery cell, the silicon negative electrode SEI film will react rapidly, and the exposed silicon negative electrode surface will generate reaction heat with the electrolyte. The reaction heat accumulation cannot be released, which will cause the temperature inside the battery cell to rise sharply until the positive electrode active materials such as lithium cobalt oxide decompose, the battery cell will catch fire or explode, and the test will fail. This failure problem is more serious than that of traditional graphite negative electrodes.
[0004] In order to solve the above safety problems, traditional technologies have attempted to improve the positive and negative electrode active materials, positive and negative electrode plates, diaphragms, electrolytes, etc. There are also technologies that attempt to increase the heat dissipation of the battery cell surface in order to release the internal temperature of the battery cell; however, the above technical directions have not yet achieved ideal technical results. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides an aluminum-plastic film that can effectively solve the safety problem of secondary batteries, especially improve the thermal abuse safety performance of lithium-ion batteries containing silicon-based negative electrode materials.
[0006] The present invention also provides a secondary battery comprising the aluminum-plastic film.
[0007] The present invention also provides an application of the secondary battery.
[0008] According to an embodiment of the first aspect of the present invention, there is provided an aluminum-plastic film, the aluminum-plastic film comprising an aluminum foil layer, an adhesive layer and a nylon layer stacked in sequence;
[0009] The adhesive layer includes adhesive points arranged in an array, and phase change materials distributed between the gaps between the adhesive points;
[0010] The phase change temperature of the phase change material is 90 to 120°C;
[0011] The nylon layer is provided with through holes.
[0012] The aluminum-plastic film according to the embodiment of the present invention has at least the following beneficial effects:
[0013] The simplified model of heat generation and heat dissipation balance of secondary batteries during operation is: Q-δ=m Cp.m(dT / dt), where Q represents the heat generation rate of the secondary battery, δ: represents the heat dissipation rate of the secondary battery, m represents the mass of the secondary battery, Cp.m represents the specific heat capacity of the secondary battery as a whole; T represents temperature, and t represents time. It can be seen that the greater the heat dissipation rate, the smaller dT / dt, which means that the heating rate of the secondary battery is slower, even 0, and the secondary battery is less likely to have problems such as thermal runaway and spontaneous combustion; that is, whether the secondary battery can withstand thermal shock and whether thermal runaway will occur is closely related to its heat dissipation rate.
[0014] Conventional aluminum-plastic films at least include an aluminum foil layer and a nylon layer stacked together, wherein the nylon layer gives full play to its mechanical properties and toughness, has low cost and good comprehensive performance, and plays a role in protecting the aluminum foil layer. In order to increase the adhesion between the aluminum foil layer and the nylon layer, an adhesive is also added between the two layers; although the aluminum foil layer has a high thermal conductivity, the thermal conductivity of the nylon layer and the adhesive is poor; therefore, the thermal conductivity of conventional aluminum-plastic films is poor overall, and the temperature inside the battery core cannot be released in time, that is, the heat dissipation rate is slow, and thermal runaway is prone to occur.
[0015] In the aluminum-plastic film provided by the present invention, the structure and material of the aluminum-plastic film are optimized: there are gaps between the adhesive points, the gaps are filled with phase change materials, and through holes are provided on the nylon layer; therefore, when the secondary battery is subjected to thermal shock and the temperature exceeds the phase change temperature of the phase change material, the phase change material changes from solid to liquid and leaks out through the through holes; at this time, the gaps between the adhesive points and the through holes on the nylon layer can form air convection, expand the heat dissipation rate of the secondary battery, and improve the thermal shock pass rate of the secondary battery, that is, improve the safety performance of the secondary battery.
[0016] Furthermore, the phase change material also has the function of absorbing heat when the secondary battery is subjected to thermal shock, thereby reducing the overall temperature of the secondary battery to a certain extent and improving its safety performance. Controlling the phase change temperature of the phase change material at 90℃~120℃ can not only ensure that the high temperature of the aluminum-plastic film will not affect the phase change material during use and top sealing (avoiding the melting, failure, or deformation of the phase change material during the top sealing process, affecting the appearance), but also absorb heat when the lithium secondary battery is subjected to hot box test, reduce its internal temperature rise, and improve the hot box pass rate.
[0017] Furthermore, the filling of the phase change material maintains the structural integrity and flatness of the aluminum-plastic film. Specifically, it maintains the flatness of the aluminum-plastic film during the punching and vacuuming process, and maintains the overall aesthetics of the secondary battery.
[0018] According to some embodiments of the present invention, the aluminum-plastic film further includes a polypropylene film layer disposed on a surface of the aluminum foil layer away from the nylon layer.
[0019] According to some embodiments of the present invention, the thickness of the polypropylene film layer is 50-60 μm, for example, about 55 μm or about 57 μm.
[0020] According to some embodiments of the present invention, the thickness of the aluminum foil layer is 30-50 μm; for example, it may be about 35 μm, 40 μm or about 45 μm.
[0021] According to some embodiments of the present invention, the gap between two adjacent adhesive points is 0.5 to 2 mm. For example, it can be about 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm or about 1.8 mm. In the present invention, the gap between the adhesive points is the shortest distance between the center points of two adjacent adhesive points.
[0022] According to some embodiments of the present invention, the projection shape of the adhesive points on the aluminum foil layer is at least one of a circle, a rectangle, a cross and an irregular shape.
[0023] According to some embodiments of the present invention, the equivalent circular diameter of the projection of the adhesive point on the aluminum foil layer is 0.3-0.8 mm, for example, about 0.5 mm or about 0.6 mm.
[0024] According to some embodiments of the present invention, the phase change point of the phase change material is 90-110°C. For example, it can be about 95°C, 100°C or about 105°C. The meaning of the phase change point is that above this temperature, the phase change material is in liquid state, and below this temperature, the phase change material is in solid state. The phase change point of the above-mentioned phase change material is lower than the thermal runaway temperature of the secondary battery, but higher than the conventional use temperature of the secondary battery; therefore, the present invention sets a corresponding phase change point, and the phase change material can not only absorb heat when the temperature is higher than the conventional use temperature to achieve the effect of lowering the temperature of the secondary battery, but also become liquid, which provides space for air convection and further increases the heat transfer efficiency of the aluminum-plastic film.
[0025] According to some embodiments of the present invention, the phase change material comprises paraffin.
[0026] According to some embodiments of the present invention, the thickness of the adhesive layer is 2-5 μm, for example, about 3 μm or about 4 μm.
[0027] According to some embodiments of the present invention, the equivalent diameter of the through hole on the nylon layer is 2-6 mm, for example, about 3 mm, 4 mm or about 5 mm.
[0028] According to some embodiments of the present invention, the shape of the through hole includes at least one of a circle, a rectangle, a cross shape and an irregular shape. The equivalent diameter refers to the diameter of a circle having the same area as the through hole.
[0029] According to some embodiments of the present invention, the through hole is disposed at a corner between the nylon layers, so that when the phase change material is melted and flows out by heat, the gap between the through hole and the adhesive point can better form air convection.
[0030] According to some embodiments of the present invention, the thickness of the nylon layer is 10-20 μm, for example, about 12 μm, 15 μm or about 18 μm.
[0031] According to some embodiments of the present invention, the method for preparing the aluminum-plastic film comprises the following steps:
[0032] S1. The adhesive point is provided on one side surface of the aluminum foil layer;
[0033] S2. Filling the phase change material in the gap between the adhesive points to form the adhesive layer;
[0034] S3. Covering the nylon layer on the surface of the adhesive layer.
[0035] According to some embodiments of the present invention, the method for preparing the aluminum-plastic film further comprises, before step S1, providing a polypropylene film layer on the other side of the aluminum foil layer.
[0036] According to an embodiment of the second aspect of the present invention, a secondary battery is provided, the secondary battery comprising the aluminum-plastic film provided by the embodiment of the first aspect of the present invention, and a battery cell wrapped and contained by the aluminum-plastic film.
[0037] Since the secondary battery adopts all the technical solutions of the aluminum-plastic film of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0038] According to some embodiments of the present invention, the battery cell includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0039] According to some embodiments of the present invention, the secondary battery further includes an electrolyte, the electrolyte infiltrates the battery core, and the electrolyte is wrapped by the aluminum-plastic film.
[0040] According to some embodiments of the present invention, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery and a potassium ion battery.
[0041] According to some embodiments of the present invention, when the secondary battery is a lithium-ion battery, the negative electrode active material in the negative electrode includes a silicon-based negative electrode material.
[0042] When the secondary battery is a lithium-ion battery, the type of the positive electrode active material in the positive electrode is not strictly limited, and can be, for example:
[0043] At least one of a polyanionic material, a layered material, and a spinel material.
[0044] The polyanion material includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0045] The general formula of the layered material is LiMO2, wherein M includes at least one of nickel, cobalt and manganese, and specifically may be at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.
[0046] In the layered material, M also includes a doping element; the doping element includes at least one of aluminum, zirconium, magnesium, titanium, boron, and fluorine.
[0047] The spinel material includes lithium manganate (spinel phase).
[0048] According to some embodiments of the present invention, the hot box temperature that the secondary battery can pass is ≥132°C; for example, it can be about 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C, 140°C or about 145°C.
[0049] According to an embodiment of the third aspect of the present invention, there is provided an application of the secondary battery described in an embodiment of the second aspect of the present invention in the fields of power batteries, energy storage batteries and 3C small household appliances.
[0050] Since the application adopts all the technical solutions of the secondary battery of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0051] According to some embodiments of the present invention, the field of power batteries includes secondary batteries for electric vehicles.
[0052] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0053] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0054] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0056] Figure 1 It is a schematic diagram of the cross-sectional structure of the aluminum-plastic film provided in Example 1 of the present invention.
[0057] Figure 2 It is a top view of the aluminum-plastic film provided in Example 1 of the present invention.
[0058] Figure 3 It is a schematic diagram of the structure of a soft-pack lithium secondary battery provided in an application example of the present invention.
[0059] Reference numerals:
[0060] Aluminum foil layer 100 , adhesive layer 200 , phase change material 210 , adhesive dots 220 , nylon layer 300 , through holes 310 , polypropylene film layer 400 . DETAILED DESCRIPTION
[0061] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0062] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0063] Example 1
[0064] refer to Figures 1-2 , this example provides an aluminum-plastic film, specifically:
[0065] The aluminum-plastic film comprises a polypropylene film layer 400, an aluminum foil layer 100, an adhesive layer 200 and a nylon layer 300 which are stacked.
[0066] The thickness of the polypropylene film layer 400 is 57 μm;
[0067] The thickness of the aluminum foil layer 100 is 40 μm;
[0068] The thickness of the adhesive layer 200 is 3 μm; the adhesive layer 200 includes adhesive points 220 distributed in an array, and a phase change material filled in the gaps between the adhesive points 200; the phase change material is paraffin with a phase change point of 100°C (the phase change temperature varies with the composition of the paraffin); the gap between the adhesive points 220 is 0.5 mm (the distance from the center point to the center point), and the projection of each adhesive point 220 on the surface of the aluminum foil layer 100 is a circle with a diameter of 0.5 mm; the material of the adhesive point is polyethylene terephthalate (PET).
[0069] The thickness of the nylon layer 300 is 15 μm, and a through hole 310 with a diameter of 2 mm is respectively opened at the diagonal positions of the nylon layer 300 .
[0070] Examples 2 to 16 and Comparative Examples 1 to 4 each provide an aluminum-plastic film, which differs from Example 1 in that:
[0071] The shapes and gaps of the adhesive points and the through holes opened on the nylon layer are different. The specific parameters are shown in Table 1.
[0072] Table 1 Partial parameters of aluminum-plastic films in embodiments and comparative examples
[0073]
[0074] In Examples 13 and 14 of Table 1, the equivalent diameter of the adhesive dots is the same as that of Example 1.
[0075] Application Examples
[0076] refer to Figure 3 , this example provides a lithium secondary battery, specifically:
[0077] Preparation of positive electrode: The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 98.1:1.1:0.8, and then coated on aluminum foil. After drying, rolling, and slitting, the positive electrode is obtained.
[0078] Preparation of the negative electrode: The negative electrode active material (a mixture of silicon-carbon material and graphite, in which silicon accounts for 10% of the mass percentage of the negative electrode material), conductive agent acetylene black, conductive agent single-arm carbon nanotube (SWCNT), binder styrene-butadiene rubber (SBR), lithiated polyacrylic acid (PAALI), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a mass ratio of 95.9:0.5:0.05:1:1.96:0.5, and then coated on a copper foil. After drying, rolling, and slitting, the negative electrode is obtained.
[0079] Diaphragm: Made of polyethylene (PE) porous polymer film.
[0080] Electrolyte: A solution prepared by mixing lithium salt LiPF6 and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP)) = 25:10:15:50, mass ratio) in a mass ratio of 8:92.
[0081] Battery cell assembly: The positive electrode, negative electrode and separator are wound to form a battery cell, where the separator is placed between the positive electrode and the negative electrode to prevent the positive electrode and the negative electrode from direct contact and short circuit.
[0082] Assembly of lithium secondary battery: placing the battery core in a bag formed by the aluminum-plastic film obtained in the embodiment and the comparative example, and then injecting electrolyte into the aluminum-plastic film and sealing it to obtain the battery.
[0083] Test Case
[0084] This example tests the safety performance of the lithium secondary battery obtained in the application example. The specific method is as follows: place the lithium secondary batteries in a constant temperature chamber at 25℃ and let them stand for 30 minutes to make the lithium secondary batteries reach a constant temperature. Charge the lithium secondary batteries that have reached a constant temperature at a constant current of 0.5C (1C current density is 6000mAh) to a voltage of 4.53V, then charge them at a constant voltage of 4.53V to a current of 0.05C, let them stand for 60 minutes, put the cells in an oven, and heat the oven to X℃ (X=126,128,130,132,134,136,138,140) at a rate of 5±2℃ / min, heat to the target temperature and keep it for 30 minutes before stopping. During the process, monitor the surface temperature of the cells, the ambient temperature and the voltage. If all lithium secondary batteries (3 per batch) do not catch fire or explode, it means that they have passed the hot box test at a specific temperature. Record the highest temperature at which the lithium secondary batteries pass the hot box test. The specific results are recorded in Table 2.
[0085] Table 2 Hot box test results of lithium secondary batteries obtained in application examples
[0086]
[0087]
[0088] Comparing Examples 1 to 4, it can be seen that as the gap between the adhesive points increases, the temperature passing through the hot box shows a trend of first rising and then stabilizing. The maximum temperature on the surface of the battery cell shows a trend of first rising and then falling. This is because the larger the gap between the adhesive points, the more paraffin is stored in the adhesive layer, the more heat can be absorbed, and after the paraffin flows out, the larger the area that can be used for heat dissipation. Therefore, in theory, the temperature on the surface of the battery cell will drop. However, as the temperature rises, the heat brought by the hot box and the heat generated by side reactions such as the electrolyte inside the battery cell add up to more and more. Therefore, in theory, the temperature on the surface of the battery cell will rise; after the two are combined, there is a trend that the surface temperature first rises and then falls; there is also a trend that the temperature passing through the hot box first rises and then stabilizes.
[0089] By comparing Examples 1 to 4, Examples 5 to 8, and Examples 9 to 12, it can be seen that when the distribution of the adhesive points remains unchanged, as the diameter of the through-holes in the nylon layer increases, the temperature through which the hot box can pass shows a trend of first rising and then flattening, and the surface temperature of the battery cell shows a trend of first rising and then falling. The reason is the same as above. Specifically, the larger the hole, the faster the paraffin flows out, the greater the rate of heat removal, and the temperature of the battery cell surface will drop. However, the external heat after the hot box temperature rises and the internal heat of the battery cell side reactions will also increase, thereby also raising the surface temperature of the battery cell. The above situation occurs after the two are combined.
[0090] By comparing Example 2 with Examples 13-14, it can be seen that changing the shape of the adhesive point has almost no effect on the temperature of the lithium secondary battery passing through the hot box, and has little effect on the maximum temperature of the battery surface. This shows that in actual production, the shape of the adhesive point can be selected according to needs and experimental equipment, that is, the production process of the aluminum-plastic film provided by the present invention has a high fault tolerance rate and is convenient for promotion.
[0091] By comparing Example 8 with Examples 15 to 16, it can be seen that, keeping other conditions unchanged, within the range provided by the present invention, the phase change temperature of the phase change material is increased, and the temperature through the hot box of the lithium secondary battery shows a trend of first increasing and then decreasing, and the maximum surface temperature shows a trend of first increasing and then decreasing. This shows that the selection of a phase change material with a suitable phase change temperature can significantly reduce the maximum surface temperature of the lithium secondary battery, and further improve the safety performance of the obtained lithium secondary battery.
[0092] By comparing the results of the embodiment and comparative examples 1 to 2, it can be seen that in the aluminum-plastic film provided by the embodiment of the present invention, there is a synergistic effect between the structural design of the adhesive layer and the nylon layer, and the combination of the two can significantly improve the thermal safety performance of the lithium secondary battery. Either one alone does not have a significant effect of improving safety performance.
[0093] By comparing the results of Example 8 and Comparative Examples 3 to 4, it can be seen that if the phase change temperature of the phase change material is not within the range required by the present invention, it does not have the effect of improving the safety of the lithium secondary battery. Specifically, in Comparative Example 3, the phase change material has failed during the formation, heat sealing, or normal use of the lithium secondary battery; in Comparative Example 4, the phase change material still does not work when the lithium secondary battery is close to the temperature of thermal runaway.
[0094] In summary, due to the special aluminum-plastic film provided by the present invention, a lithium secondary battery with good thermal safety performance is obtained; therefore, the obtained lithium secondary battery and other secondary batteries are expected to be widely used in the fields of power batteries, energy storage batteries or 3C small household appliances.
[0095] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. An aluminum-plastic film, characterized in that: The aluminum-plastic film comprises an aluminum foil layer, an adhesive layer and a nylon layer which are stacked in sequence; The adhesive layer includes adhesive points arranged in an array, and phase change materials distributed between the gaps between the adhesive points; The phase change temperature of the phase change material is 90 to 120°C; The nylon layer is provided with through holes.
2. The aluminum-plastic film according to claim 1, characterized in that: The aluminum-plastic film also includes a polypropylene film layer arranged on the surface of the aluminum foil layer on a side away from the nylon layer.
3. The aluminum-plastic film according to claim 1, characterized in that: The phase change material includes paraffin wax.
4. The aluminum-plastic film according to claim 1, characterized in that: The gap between two adjacent adhesive points is 0.5-2 mm; and / or the projection shape of the adhesive points on the aluminum foil layer is at least one of a circle, a rectangle, a cross and an irregular shape.
5. The aluminum-plastic film according to claim 1, characterized in that: The equivalent diameter of the through holes on the nylon layer is 2-6 mm.
6. The aluminum-plastic film according to any one of claims 1 to 5, characterized in that: The thickness of the adhesive layer is 2-5 μm.
7. A secondary battery, characterized in that: The secondary battery comprises the aluminum-plastic film according to any one of claims 1 to 6, and a battery cell wrapped and contained by the aluminum-plastic film.
8. The secondary battery according to claim 7, characterized in that: The secondary battery includes at least one of a lithium ion battery, a sodium ion battery and a potassium ion battery; and / or the battery cell includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
9. The secondary battery according to claim 8, characterized in that: When the secondary battery is a lithium ion battery, the negative electrode active material in the negative electrode includes a silicon-based negative electrode material.
10. Application of the secondary battery according to any one of claims 7 to 9 in the fields of power batteries, energy storage batteries and 3C small household appliances.
Citation Information
Patent Citations
Battery packaging film and preparation method thereof, and lithium ion battery
CN111354880A
Composite phase change material, application method thereof, and battery
CN111793471A
Production process of lithium battery aluminum plastic film
CN117183417A
Flame-retardant heat dissipation type aluminum plastic film and preparation method thereof
CN117445447A
Compound outer plastic -aluminum membrane
CN207199678U